The Development Strategy Of Halal Nature Tourism Based On The Empowerment Of Bangka Belitung Coastal Community - Heriyanni Mashithoh; Andy Mulyana; Rulyanti Susi Wardhani (Fakultas Ekonomi, Universitas Bangka Belitung, 2021)
The purpose of this research is to identify internal and external factors and analyze the strengths, weaknesses, opportunities and threats in developing halal ecotourism based on the empowerment of coastal communities in Bangka Belitung. Furthermore, a strategy for development is formulated by minimizing weaknesses and threats, maximizing utilization of opportunities and strengths. The background of this research departs from the complaints of Muslim tourists when visiting a region or country that they doubt the halalness of food and the lack of available places of worship and the trend of world tourism based on nature and environmentally friendly. The locus chosen in this study was the Province of Bangka Belitung Islands. The potential of an archipelagic province with exotic beaches and one of the largest fish producers, makes fishermen and coastal communities dependent on marine products and their products. This research is a qualitative descriptive study. The results obtained in this study are the need for community empowerment in the development of tourism products in accordance with local government regulations and policies as well as the values of politeness and morality, the development of marketing for halal nature tourism programs and the physical, social, cultural and economic environment of the community.